2010
DOI: 10.1128/cvi.00199-10
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dense Granule Antigen GRA6 in an Immunoglobulin G Avidity Test To Exclude AcuteToxoplasma gondiiInfection during Pregnancy

Abstract: The usefulness of a specific immunoglobulin G (IgG) avidity enzyme-linked immunosorbent assay (ELISA) based on recombinant GRA6 antigen for distinguishing between acute and chronic Toxoplasma infection was investigated. Two sets of serum samples obtained from pregnant women with acute, chronic, or no Toxoplasma infection collected in France and Iran were used. Among the French subjects, 19 of 20 (95%) women who experienced seroconversion during the past 4 months before sampling displayed low-avidity IgG antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
0
15
0
4
Order By: Relevance
“…ROP1 recombinant antigen was also applied in an IgG avidity test (62), where specific low-avidity antibodies were detected in most of the sera from individuals with acute toxoplasmosis, while the absence of specific antibodies or high-avidity antibodies was detected in sera from patients with chronic infection. Furthermore, in 2010, Elyasi et al (63) showed better clinical usefulness for an IgG avidity assay based on recombinant GRA6 than for the Euroimmun avidity test (Euroimmun, Lübeck, Germany) for the exclusion of recent infection, occurring less 4 months previously, in pregnant women.…”
Section: T Gondii Recombinant Antigensmentioning
confidence: 99%
“…ROP1 recombinant antigen was also applied in an IgG avidity test (62), where specific low-avidity antibodies were detected in most of the sera from individuals with acute toxoplasmosis, while the absence of specific antibodies or high-avidity antibodies was detected in sera from patients with chronic infection. Furthermore, in 2010, Elyasi et al (63) showed better clinical usefulness for an IgG avidity assay based on recombinant GRA6 than for the Euroimmun avidity test (Euroimmun, Lübeck, Germany) for the exclusion of recent infection, occurring less 4 months previously, in pregnant women.…”
Section: T Gondii Recombinant Antigensmentioning
confidence: 99%
“…18,21 In this study, two T. gondii cDNA phage clones that expressed proteins with the potential to be used in IgG avidity assay were identified. The corresponding purified recombinant antigens were produced and their effectiveness in IgG avidity assays was assessed.…”
Section: -21mentioning
confidence: 99%
“…15 These include surface antigens (SAG), [17][18][19][20] dense granule antigens (GRA), 17,18,20,21 microneme protein (MIC) 18 and rhoptry antigens (ROP). 20,38 Proteins encoded by AG12b and AG18 belong to none of the above-reported groups since a different approach was used in the present study.…”
Section: 37mentioning
confidence: 99%
“…Zato je bitno da se, korišćenim testovima, mogu dokazati antitela IgM klase (kao pokazatelji akutne infekcije) i antitela IgG klase. relativno svežoj infekciji) [18,19]. ELISA test i RVK metoda) [13,14].…”
Section: Diskusijaunclassified